Media Campaign Advocacy Supporting Indonesian Ianfu Survivors: A Postfeminist Perspective - Kania Bening Rahmayna (Salasika, 2022)
Ianfu is a system of sexual slavery during the Japanese occupation in Indonesia on 1942-1945. Ianfu is interested in researching from the point of view of one of the theories in Feminism, namely the theory of Postfeminism. The purpose of writing this article is for two reasons, first, ianfu is one of the historical facts of Indonesia which is still unresolved. Second, with this article, I hope that more people will know about Ianfu. In addition, this paper was also prepared to fulfill the final semester assignment for the Gender Feminism Course. The method I use in this paper is the Literature Study Method where data collection is directed at searching for data and information through reading documents, both written documents and electronic documents. The results of this study indicate that even though the Japanese have been found guilty in the International Court of Justice in The Hague of the Netherlands for war crimes. The Japanese side still hasn't officially apologized to the Ianfu survivors in Indonesia.